Reduction effect of oral pravastatin on the acute phase response to intravenous zoledronic acid: protocol for a real-world prospective, placebo-controlled trial. Issue 7 (13th July 2022) - Liu, Qi; Han, Gengyu; Li, Runting; Fan, Dongwei; Du, Guohong; Zhang, Min; Tao, Liyuan; Li, Haiyan; Liu, Dongyang; Song, Chunli
Abstract : Introduction: Zoledronic acid (ZA) has been used as a first-line treatment in patients with osteoporosis (OP) who receive an annual injection of 5 mg. However, side effects of bone pain and fever, known as the acute phase response (APR), have often been observed after clinical usage. A meta-analysis reported that the incidence of APR was 49.4% among patients with OP who received ZA for the first time and that 30% of patients with these adverse effects refused treatment in the following year. As a clinically used hypolipidaemic drug, statins can inhibit 3-hydroxy-3-methylglutaryl coenzyme A reductase to block the pathway upstream of farnesyl pyrophosphate synthase. This process can decrease the accumulation of isopentenyl pyrophosphate to prevent γδT-cell activation and inflammatory factor production, blocking APR occurrence. The aim of this study is to determine the reduction effect of oral pravastatin on APR and investigate the possible mechanisms underlying the effect in vivo. Methods and analysis: This will be a single-centre, placebo-controlled trial. Female participants will be allocated at a 1:1 ratio to receive either oral pravastatin or a placebo at 1-hour predose and 24 and 48 hours post-administration of ZA. The primary outcome will be the incidence of APR within 72 hours after ZA infusion. The secondary outcomes will include the occurrence time and severity of APR and the frequency and amount of acetaminophen usage within 72 hours after ZA infusion. This study will determine the preventive effect of oral pravastatin on APR in Chinese patients with OP, supporting the clinical application of ZA to alleviate concerns regarding safety and increase patient compliance. Ethics and dissemination: This study protocol has been registered with ClinicalTrials.gov. This study protocol was reviewed and approved by the Peking University Third Hospital Medical Science Research Ethics Committee. The results will be published in scientific peer-reviewed journals. Trial registration number: NCT04719481 .